The double injection technique to improve visualization of severe coronary lesions with optical coherence tomography. Issue 5 (3rd March 2022) - Rivero, Fernando; Marco, Valeria; Biccirè, Flavio Giuseppe; Budassi, Simone; Cuesta, Javier; del Val, David; Bastante, Teresa; de la Fuente, Hortensia; Prati, Francesco; Alfonso, Fernando
Abstract: Background: Optical coherence tomography (OCT) is a high‐resolution imaging modality that provides a precise evaluation of coronary anatomy. However, the presence of severe coronary lesions can prevent the required adequate distal contrast flushing resultting in inadequate blood clearance and poor image quality or complete blood shadowing of the underlying vessel wall. Objectives: The aim of this prospective study was to evaluate the feasibility and safety of a novel "double injection technique" (DIT) to overcome the limitations of the conventional technique (CT) in patients with severely stenotic lesions. Methods: Twenty‐three patients with severe angiographic lesions were sequentially imaged before intervention with OCT with the CT and then with DIT. A total of 5125 OCT frames were carefully matched and analyzed by an independent central core lab. A semiquantitative image quality score was used to grade the number of quadrants (0–4) with vessel wall visualization. Results: Optimal OCT visualization (Grades 3–4) significantly improved by the DIT (68% vs. 38% of frames, p < 0.001). The DIT also improved the mean score (3.1 ± 0.6 vs. 2.0 ± 0.8; p < 0.05; mean improvement of 1.1 ± 0.5 per patient). There were no complications associated with the DIT. Conclusion: The DIT significantly improved preintervention image quality of OCT in severe coronary lesions.